Efeito do verniz de clorexidina 40% sobre microorganismos periodontopatogênicos e no aumento gengival em pacientes ortodônticos. estudo prospectivo "split mouth" - Henrique Pretti (2010)
The increase in gingival volume is a large group of alterations, both from cell component and fibrous periodontal tissue. The etiology of the increase in gingival volume is diverse and ranges from acute or chronic inflammatory processes caused by local irritating factors, systemic disorders, heredity, anatomical or as a side effect of drug therapies. The widespread gingival overgrowth is commonly caused by inflammatory response to plaque, which is very common in orthodontic patients. The aim of this study is to analyze the effects of varnish containing chlorhexidine (40%) in the bacterial flora of the gingival sulcus and increase gingival volume changes in patients with braces. The sample consisted of 30 patients with gingival overgrowth from the Clinic of the Specialization Course in Orthodontics, School of Dentistry, Federal University of Minas Gerais. For each individual a sample from the buccal gingival sulcus of the right and left upper second premolars were collected. After the first clinical exam and prophylaxis, a chlorhexidine varnish was applied on molars and premolars at on one side of the upper jaw and the other side was applied a varnish without chlorhexidine, being used as controls. The qualitative and quantitative analysis of bacteria, Eikenella corrodens, Prevotella intermedia and Fusobacterium nucleatun, were performed by polymerase chain reaction (PCR) in real time before applying the varnish (T0), 14 days (T14) and 56 days after applying it (T56). In these three periods the premolars were photographed and the vestibular areas of the crown were measured. Analyzing the photographs, the mean areas of the treated side were higher at T14 and T56 while at T0 no difference among the means of treated and control sides were seen. In the control, the mean area remained the same at T0 and T14, decreasing at T56. On the treated side, the average area increased with time: the smallest measure at T0 and the highest at T56. Regarding the result of changes in the analyzed bacteria, no statistical differences were found between T0, T14 and T56 on the control and the treated side.Conclusion: The use of the clorexidina varnish EC40 decreased the inflammation gengival in a progressive way to 14 and 56 days after the application and the number of the studied bacteria didn't suffer significant changes, demonstrating that the control of the bacterial plate for chemical agents is more complex and evolve other factors that should be studied.